Kepemimpinan Visioner dalam Peningkatan Mutu Pendidikan: Studi Kasus di Madrasah Aliyah Negeri Insan Cendikia (MAN IC) Serpong Tangerang Selatan - Moh. Toha (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Quality madrasahs can be formed through visionary leadership management, as it can see the potential and future opportunities of the institution. This research aims to describe visionary leadership management in planning (formulating vision), organizing (empowering human resources), and applying the vision in madrasahs to be on target. A qualitative method with a case study approach was used in this research. Data collection was carried out using interview, observation, and documentation techniques, while data analysis was performed through data reduction, data processing, and conclusion drawing, as well as data validation using triangulation. The research results found that the Head of Madrasah Aliyah Negeri Insan Cendekia (MAN IC) Serpong, South Tangerang, was able to formulate a future-oriented vision based on his personal and spiritual values. The formulated vision is focused, realistic, and progressive. Possessing high loyalty, and the ability to participate in mentoring, receiving input, complaints, and ideas from teachers for the sake of creating a sense of ownership towards the madrasah's vision. The formulated vision can be implemented through curriculum, programs, and habits based on spiritual values. The achievement of the vision is not instant but is designed through stages of mature and continuous planning. Thus, with this visionary leadership approach, madrasahs are not only directed towards achieving academic and religious achievements but also forming an integrated, harmonious, and adaptive educational ecosystem to the changes of the times. Visionary leadership is proven to be an important key in creating a quality and globally competitive educational environment.